2009
DOI: 10.1021/es9000328
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Retinoic Acid Receptor Agonists in Sewage Treatment Plants

Abstract: Retinoic acid receptor (RAR) agonists are speculated to be one possible cause for the widely observed frog deformities in North America, although little is known about the specific RAR agonists in aquatic environments. We identified the specific RAR agonists in sewage treatment plants (STPs) and receiving rivers using an RAR yeast two-hybrid bioassay. Water samples were extracted by solid-phase extract cartridges, which were successively eluted by hexane, ethyl acetate, and methanol for bioassay. Among the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 37 publications
6
34
5
Order By: Relevance
“…S2), which was greater than those (0.7 ± 0.8 ng/L) reported previously in a river basin, Liaodong Bay, China, where untreated wastewaters are discharged directly into the rivers (29). The greatest total concentration of RAs and 4-oxoRAs in water from Taihu Lake was 2.0 × 10 ng/L, which was comparable to concentrations in raw influents of sewage treatment plants (28). Taihu Lake is an important drinking water source for local residents, and domestic wastewaters without treatment are not directly discharged into the lake.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…S2), which was greater than those (0.7 ± 0.8 ng/L) reported previously in a river basin, Liaodong Bay, China, where untreated wastewaters are discharged directly into the rivers (29). The greatest total concentration of RAs and 4-oxoRAs in water from Taihu Lake was 2.0 × 10 ng/L, which was comparable to concentrations in raw influents of sewage treatment plants (28). Taihu Lake is an important drinking water source for local residents, and domestic wastewaters without treatment are not directly discharged into the lake.…”
Section: Resultsmentioning
confidence: 53%
“…RAs and their metabolites can enter into the aquatic environments through discharge of domestic sewage. Concentrations of RAs and their bioactive metabolites 4-oxo-RAs in treated wastewater have generally been found to be less than 1.0 ng/L (28,29). Recently, anomalous concentrations of RAs and 4-oxoRAs (up to 20 ng/L) were measured in some protected drinking water sources (30), which suggested that there might be unidentified sources of RAs in aquatic systems.…”
mentioning
confidence: 99%
“…We investigated the RARα agonistic activity in seven WWTPs and their receiving rivers (Tonghui River and Qing River) and detected a significant activity mainly in the ethyl acetate fraction (medium polar fraction) of the wastewater and water samples. 40) The maximal atRA equivalents (atRA-EQ) in the fraction estimated based on the results of yeast two-hybrid assay were 13.4, 3.2 and 10.0 ng/l in WWTP influent, WWTP effluent and river water, respectively, which were much lower than the atRA concentration exhibiting teratogenic effects in animals ( Table 1). Most of the RARα agonistic activity detected in river water seemed to be explained by WWTP effluents and untreated wastewater discharged from several wastewater discharging pipes.…”
Section: Findings Of Rar Agonist Contamination In the Aquatic Environmentioning
confidence: 98%
“…Oxidative metabolites of RA in humans and animals such as 4-oxo-RA, 4-hydroxy-RA, 18-hydroxy-RA and 5,6-epoxy-RA can bind to RARs and activate the RAR-mediated transcription via an RA response element. 28,[38][39][40] In particular, 4-oxo-RAs such as 4-oxo-atRA and 4-oxo-13-cis RA (4-oxo-13cRA) have been proven to have RAR agonistic activity equivalent to atRA using different in vitro bioassay systems. 28,38,40) Furthermore, numerous studies have demonstrated that these RA metabolites exhibit RAR-mediated biological activity just as RA does.…”
Section: Natural and Xenobiotic Compounds That Act As Rar Agonistsmentioning
confidence: 99%
See 1 more Smart Citation